Historic real estate : market morality and the politics of preservation in the early United States - Martinko, Whitney (Early American studies., 2020)
"This book discusses historic preservation in the early United States. It argues that the history of preservation is a crucial component of the history of American capitalism. U.S. residents shaped the landscape of "modern" capitalism by cultivating dynamic forms of permanence as well as architectural innovation, new construction, and urbanization. This view of the early national built environment disrupts the clean narrative of the privatization of public space to which preservationists, environmentalists, and urbanists sometimes subscribe. Early U.S. advocates of architectural preservation claimed to limit the influence of market mentality on the built environment. But their methods of securing environmental permanence have confounded distinctions between public and private since the eighteenth century. To confront the history of this entanglement is to see historical consciousness at the heart of defining commodity production, consumption, and the value of labor in the past and in the present"--